LEGITIMASI PEMUNGUTAN JIZYAH DALAM ISLAM: OTORITAS AGAMA DAN PENGUASA - Dedy Sumardi (Sharia and Law Faculty, 2017)
Jizyah is obliged to Non Muslim ahl dhimmah status as a voluntary compensation for protection both internally and externally. The legitimacy of the poll voting procedures derived from sources